Trust at stake: Is the "dual mission" of the U.S. Alzheimer's Association out of balance?. (July 2019) - Caspi, Eilon
The official vision of the U.S. Alzheimer's Association is "A world without Alzheimer's disease." The "dual mission" of the organization is "to eliminate Alzheimer's disease through the advancement of research and to enhance care and support for individuals, their families and caregivers." Using numerous reports from leading researchers and practitioners, a case is made by which the "dual mission" is grossly unbalanced with predominant focus on biomedical research aimed at curing the disease compared to research and practices focused on the psycho-social impacts of and adaptations to living with it. These experts discuss the likelihood of curing the disease, the complexity of realizing this goal, and the urgent need to "bring back the social and psychological aspects" of living with dementia to center stage. The moral responsibility to balancing the "dual mission" in accordance with the original motivation of the grassroots organizations who formed the association in 1980 is discussed.